Aplicación de contabilidad comercial en el automotriz “Reina del Cisne”, periodo octubre a noviembre del 2014, del cantón Yantzaza, provincia de Zamora Chinchipe - Sucunuta Morocho, Janela Carolina (2015)
The development of this research work was carried out based on the general objective: commercial accounting application in Automotive "Reina del Cisne" October-November period of 2014, the canton Yantzaza province of Zamora Chinchipe. Thus fulfilling the specific objectives, development begins with the registration, classification and interpretation of daily transactions taking place in the automotive "REINA DEL CISNE," which led to the preparation of accounting documents and the journal, book greater, trial balance to the preparation of financial statements; in order to provide information on their financial situation at the end of an accounting period, it determined that as a result run the company generates a negative value, which when knowledge would enable its owner to take measures to optimize the management financial and subsequently extend its business prospects. The methodology used for the development and study of the research work begins with the use of direct observation and interview to collect and gather information, which is analyzed, classified and sketched to proceed with the jornalización, majorization and then the presentation of states financial. By the results it was concluded that the application of the accounting system in the Automotive, is an essential tool for economic and administrative management of the business for which it is recommended to continue with the application of the accounting process applied